Cultural Dictionary of Meranao (Asia Pacific Journal of Social Innovation, 2024)
This study collected 2,000 lexical items which served as entries of a Meranao cultural dictionary that has the following objectives: 1) to present culture-related Meranao words; (2) to give the Filipino and English translations of the Meranao words; (3) to define and/or explain the items in English; (4) to provide a grammatical sketch of the Meranao language; and, (5) to present a pronunciation guide of the Meranao language. The study used a qualitative ethnographic method where majority of the data were collected through community immersion and/or observation and interviews. The elicited data served as the corpus of the study. This corpus was translated to Filipino and English to form the lexicographic data of the study. The collected Meranao words were then categorized under 22 semantic domains, namely, Physical World, Mankind, Animals, Body Parts and Functions, Food and Drink, Clothing and Adornment, Dwelling and Furniture, Agriculture and Vegetation, Physical Acts and Materials, Motion and Transportation, Possession and Trade, Spatial Relations, Quantity and Number, Time, Sense and Perception, Emotion, Mind and Thought, Language and Music, Warfare and Hunting, Law and Judgment, Social Relations, and Religion and Beliefs. The lexemes under each of these semantic categories were transcribed using the International Phonetic Alphabet IPA) and were defined in English.